Financial Knowledge, Self-Efficacy, and Financial Well-Being: The Role of Digital Inclusion in Indonesia - Hesniati, H.; Anggriani, A.; Suprapto, Yandi; Arviano, Hengky (Manunggal Halim Jaya, 2026)
This research examines the role of financial knowledge and self-efficacy in shaping financial well-being, with digital financial inclusion tested as a mediating factor. Survey data were collected from 407 Indonesian respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both financial knowledge and self-efficacy significantly influence digital financial inclusion. Digital financial inclusion, in turn, positively affects financial well-being. Self-efficacy also directly improves financial well-being, whereas financial knowledge shows no direct impact. Instead, financial knowledge indirectly contributes to financial well-being through digital financial inclusion, underscoring the mediating role of digital access. This study adds to the financial behavior literature by highlighting digital financial inclusion as a crucial channel that converts capability into improved outcomes, and by showing that self-efficacy plays a stronger role than knowledge alone. The findings suggest that policies and programs should go beyond literacy campaigns to also strengthen financial confidence and digital readiness, particularly among younger groups and vulnerable communities. The study is limited by its reliance on self-reported, cross-sectional data and its focus on the Indonesian context, which may constrain causal inference and limit the generalizability of the results.